War journal of the Second Russian Fortress Artillery Regiment of Erzeroum from its formation until the recapture of Erzeroum by the Ottoman army, March 12th. 1918 - Tverdohlebov, Vladimir Nikolaeviç, 1876-1954.‏. ([y.y.])
36 s.